THE URGENCY OF SIYAQ (INTERPTRETATION OF THE WORD AL-INS AND BASYAR PERSPECTIVE OF AR-RAGHIB AL-ASHFAHANI) IN KITAB AL-MUFRODAT FI GHARIB AL-QUR'AN - Andri Arungga Sweta; Muhammad Hamzah Syubly bin Abd Hadi Kamil; Aman Ullah; Nematullo Mukhamedov (QiST: Journal of Quran and Tafseer Studies, 2022)
Muhammad bin Idris as-Syafi'I said "Arabic has a rich vocabulary that allows mutaradif (synonyms), especially the vocabulary of the Qur'an. Al-Sibawayh said that there are the synonyms in the Qur'an, that dialogue between Arabian and others so many diversity of Arabic vocabulary. The argument is that one Qur'anic memorization does not contain the wisdom of another memorization, while Allah uses different terms for each memorization even though they explicitly have the same meaning. The problem of this research is Abu Hilal Askari said that the synonyms in the Qur'an there are different fundamentals, Also Ar-Raghib al-Asfahani said the difference between synonyms and means are implicit. The aim of this study is to analyze the implicit meaning between the words al-Ins and Basyar from the perspective of ar-Ragihb al-Ashfahani as an indicator that the mutaradif in question is found in the Qur'an so as to display the wisdom of the Qur'an. The methods of this research are qualitative method, using Library Research and inductive approach method. The results of this research are to find the explanation that ar-Raghib al-Asfahani uses the power of Siyaq Lughawi (textual explanation) in interpreting the verses, and placing the means of verses in order of language indicators. The theory of siyaq lughowi is used to analyze Ar-Ragihb al-Ashfahani's tafseer, the word of al-ins that refers to QS. al-Furqon: 49, an-Nisa: 6, and an-Nuur: 27 as the main meaning of interpretation. That verses has implicit means of inner human's characteristics: forgetfulness, calm, obey of command, and social creatures. But to explain the word of Basyar refers to QS. al-Furqon: 54, Shad: 71, al-Mudatsir: 25, al-Qomar: 24, Yasin: 15, al-Mu'minun: 47, al-Kahf: 110, al-An'aam: 50, ali-'Imran: 47, Maryam: 17, and Yusuf: 31. That verses has implicit of physically characteristic of humans: anatomy, biology, and human materials (skin, blood and etc).